Sesbagrandiflorain F, a New 2-Arylbenzofuran from the Stem Bark of Sesbania grandiflora L. - Mulyadi Tanjung*, .- (Korean Society of Pharmacognosy, 2021)
Sesbagrandiflorain F (1), a novel 2-arylbenzofuran, and two more 2-arylbenzofurans (2-3), were isolated from the stem bark of Sesbania grandiflora L. Based on information HRESIMS data, 1D, and 2D NMR spectra, the structure of 1 was fully assigned. Compounds 1-3 were tested for cytotoxicity in MCF-7 and HeLa cells. Compounds 1 and 3 showed moderate activity against MCF-7 cells with an IC50 value of 2.68 and 4.08 ㎍/mL, respectively. Conversely, all of the isolates were inactive towards HeLa cells.